2019
DOI: 10.1096/fj.201801416r
|View full text |Cite
|
Sign up to set email alerts
|

The cytokine environment influence on human skin‐derived T cells

Abstract: Skin resident T cells provide immediate immunologic responses at their specific location and play a role in the pathogenesis of skin diseases such as psoriasis. Recently, IL-9–producing T cells were described as a major T-cell subtype present in the skin, but knowledge on the biology and in situ regulation of this T-cell subtype is scarce. Here, we investigated the cytokine influence on skin T cells with focus on IL-9–producing T cells because a better understanding of their biology may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
0
5
0
1
Order By: Relevance
“…Extensive studies have revealed that chronic inflammatory dermatoses are characterized by unfavorable keratinocyte proliferation and differentiation. As a central player of persistent skin inflammation, IL-9 has also been implicated in the pathogenesis of psoriasis and other inflammatory skin diseases (Baeck et al, 2018;Gutin et al, 2016;Hong et al, 2015;Kienzl et al, 2019;Ma et al, 2014;Midde et al, 2021;Ruiz-Romeu et al, 2018;Sismanopoulos et al, 2012). Studies in K14 CRE/ERT Il9ra ∆/∆ mice with inflammatory skin diseases clarified the functional significance of IL-9RA in keratinocytes during the development of corresponding skin lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have revealed that chronic inflammatory dermatoses are characterized by unfavorable keratinocyte proliferation and differentiation. As a central player of persistent skin inflammation, IL-9 has also been implicated in the pathogenesis of psoriasis and other inflammatory skin diseases (Baeck et al, 2018;Gutin et al, 2016;Hong et al, 2015;Kienzl et al, 2019;Ma et al, 2014;Midde et al, 2021;Ruiz-Romeu et al, 2018;Sismanopoulos et al, 2012). Studies in K14 CRE/ERT Il9ra ∆/∆ mice with inflammatory skin diseases clarified the functional significance of IL-9RA in keratinocytes during the development of corresponding skin lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The resident T cells are sustained at the site of inflammation by Jak1-and Jak3-dependent cytokines IL-2, IL-7, and IL-15 (Kienzl et al, 2019). Pathogenic Th17 T cells are triggered and sustained by IL-23 (Lee et al, 2012), which signals via TYK2/Jak2 (Lowes et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…CXCL8 receptors are found in keratinocytes of psoriatic lesions, and CXCL8 activates keratinocytes through autocrine secretion, and produces and releases in ammatory mediators, which contribute to the migration of neutrophils to the lesion site [18,19]. Some studies have shown that CXCL8 protein levels are positively correlated with PASI scores, further suggesting that CXCL8 may be closely related to the severity of psoriasis.…”
Section: Discussionmentioning
confidence: 99%